The Complete Book of Soft Furnishings - Coetzee, Karen; Bergh, Rene (London New Holland Publishers Ltd., 2000)
This text contains projects which should add the finishing touch to home furnishings. It gives a fully-illustrated, step-by-step guide to making lined and unlined curtains, cafe curtains, pelmets and tiebacks, blinds, cushions and more. Also provided is a guide to special techniques.
Include Color Illustrations, Glossary and Index.
Keywords: Sewing -- Household linens -- House furnishings